The Effect of Insertion Angle on Primary Stability of Orthodontic Mini-implants "An Experimental in vivo Study" - Saba H Al-Zubaidi (University of Mosul, College of Dentistry, 2013)
Aims: To determine whether obliquely inserted mini-implants can be loaded immediately with light orthodontic force? And which mini-implants are more stable those with 90 degree or 60 degree insertion angles? Materials and Methods: three rabbits were used in this study. Sixteen mini-implants divided into 2 groups equally. The first group implanted in the rabbit's tibia bone at 90 degree insertion angle and the second group implanted in the rabbit's tibia bone at 60 degree insertion angle. The stability of mini-implants was measured using periotest device immediately before and after loading and after 2 weeks of loading period. The data were analyzed using descriptive statistic, Analysis of variance (ANOVA), Duncan Multiple analysis range test and student t-test. Result: mini-implants at 60 degree insertion angle can be loaded immediately with light orthodontic force. Also, those miniimplants having a significant greater stability before loading and after two weeks of loading period in comparison with mini-implants implanted at 90 degree angle. Conclusions: In clinical practice, miniimplants inclined to the bone surface at 60degree tend to have better primary stability and can be loaded immediately.